Women For: Newsletter (1976)
The May–June 1976 Women For: newsletter urges voters to "raise, rather than lower" their expectations and outlines the organization's endorsements and ballot positions for the June 8 primary election. It recommends selected candidates for U.S. House, California State Assembly (including Jane Tolmach in the 36th A.D.), and State Senate, while declining to endorse in the presidential or U.S. Senate races. The issue strongly supports Proposition 15, the Nuclear Safeguards Initiative, arguing that nuclear power poses serious safety, waste storage, insurance, and evacuation risks. It also backs local transit funding measures (Propositions R & T) to secure federal support for a Los Angeles rapid rail system. Additional sections report on education advocacy, community college reform, upcoming meetings, and ongoing grassroots organizing efforts.